Revisited Pulmonary Hypertension - Banerjee, Sajal Krishna; Hoque, Harisul; Zaman, SM Mustafa (University Heart Journal, 2015)
Abstract not available University Heart Journal Vol. 10, No. 2, July 2014; 53-54